If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u = 4u + 11 Reorder the terms: 5u = 11 + 4u Solving 5u = 11 + 4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-4u' to each side of the equation. 5u + -4u = 11 + 4u + -4u Combine like terms: 5u + -4u = 1u 1u = 11 + 4u + -4u Combine like terms: 4u + -4u = 0 1u = 11 + 0 1u = 11 Divide each side by '1'. u = 11 Simplifying u = 11
| X(32/x) | | 8-3/5v=-7 | | (32/x) | | 5.87x+11.74=23.48 | | 0.08x=-6.4 | | 4q+1=4q-9 | | x-3(-1)=4 | | 6.6(x-1)=-0.4x+35.4 | | 2+r=7 | | 73-4=2 | | 6.67x+100=44.4889+10x | | -2y+7=77 | | 1=1/4x | | 5w-9w=56 | | 5+1*2= | | 27*3.14=3.14n | | -4t+9=105 | | 1+1*5= | | 1+1*2= | | -7=-y+1 | | 0=4x^3+24x^2+36x | | 2x+4=5(x+1)-3(x+3) | | x+50=x+85 | | -z-6=6 | | -0.1(-27.6-2x)=0.5x | | 1/x=.12345678901234567890 | | 9x-25=180 | | -a+7=53 | | b=3+b | | x^2+2x=x+4 | | -5(0.4+0.2y)+y=-2 | | -9(a+12)=45 |